Innovatif Engineering Strategies for Revenue Growth : a SWOT and QSPM Analysis of UD AMJ Jaya Teknik - Alif Putra Awanda; Elly Ismiyah; Akhmad Wasiur Rizqi (Advance Sustainable Science Engineering and Technology, 2023)
Business competition in the current era of globalization is very rapid, so it is increasing competition between companies which is getting higher and tighter. UD AMJ Jaya Teknik is a company in the field of turning and manufacturing spare parts. As long as the business run by UD AMJ Jaya Teknik experiences a decline in income, good and appropriate strategic management is needed for UD AMJ Jaya Teknik. The methods used in this research are the SWOT and QSPM methods. The aim of this research is to provide strategy suggestions for companies to experience increasingly rapid increases in income. The four stages carried out are the stage of looking for internal and external company factors, the IFE and EFE matrix stage, the SWOT matrix matching stage, the stage of determining the main strategy with the largest total attractive score using QSPM. There are 7 proposed marketing strategies for UD AMJ Jaya Teknik. Improving the quality of the products produced and innovating the products produced is the strategy with the highest TAS score of 5.95.